Mapping the Research Trend in Economic Justice: A Bibliometric Analysis in Public Administration Perspective - Gibreel Musa Saleh, Husny; Rahimjon, Dilbarova Malika; Yosif, Mohamed Alamin Ibrahim; Mohamed, Amir Alhadi Ahmed (JIAN (Jurnal Ilmiah Administrasi Negara), 2024)
The paper emphasizes the development of academic activity in the topic of economic justice in public administration perspective over the last ten years by presenting a bibliographic analysis of research trends in this area. The study's objectives are to measure the amount of research produced, evaluate the influence of economic justice research by looking at journal impact factors and citation trends, and pinpoint important topics and networks of cooperation among scholars. The study, which makes use of data from the Scopus database, shows a large increase in the number of publications on economic justice, with important contributions coming from researchers in Australia, the United States, and the United Kingdom. Four main research areas are identified by the study, with an emphasis on socioeconomic determinants, human development, social justice, and health policy. The findings highlight the value of network analysis tools such as VOSviewer in mapping the body of knowledge in the field of economic justice research and provide insightful information for further study in this area. The need of ongoing research cooperation is emphasized in the study's conclusion in order to improve the comprehension and implementation of economic justice concepts worldwide